Emotional Intelligence as predictor of students' academic performance / Wong Sook Khuan and Pouline Koh Chai Lin - Sook Khuan, Wong; Chai Lin, Pouline Koh (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
Malaysian students have come a long way to achieve their academic results and yet failed to utilise the knowledge gained when they enter the working world. The lack of soft skills and emotional intelligence among these students dampened the situation further. These students are also known to have high memorisation skills instead of a good grasp and understanding of the concepts behind the knowledge. Hence, this study examines whether emotional intelligence can predict students' academic performance as measured by Grade point Average (GPA). Overall emotional intelligence, along with its five elements including self-awareness, self-regulation, self-motivation, social awareness and social skills, is further investigated. Survey questionnaires are employed and distributed among 300 Business and Engineering undergraduate students from two higher education institutions. Through regression analysis, results revealed that four out of five elements could predict students' academic performance as measured by GPA. Interestingly, social awareness was the only element found not able to predict students' academic performance. This study underlined the need for emotional intelligence to be incorporated into the higher education system. It is proposed, therefore, for institutions to introduce emotional intelligence in teaching and learning at the higher level as an essential unit of students' learning. This can be incorporated as part of the curriculum structure as subjects or part of co-curricular activities.